c-index and Subindices of the h-index: New Variants of the h-index to Account for Variations in Author Contribution - Post, Alex (Cureus, 2018)
Objectives Bibliometrics are used to assess or compare the academic productivity of individuals or groups. Most of these metrics, including the widely used h-index, do not recognize the added contribution that is generally provided by authors listed first, second, second-to-last and last (enhanced positions) in a publication citation. We propose the c-index as a novel modification to the h-index that will better reflect an individual’s academic output, incorporating authorship position. Methods One hundred and sixty-six academic neurosurgeons in eight New York City (NYC) metropolitan region training programs were identified through department websites. Using the Scopus citation database, bibliometric profiles were created for each surgeon. Once an individual’s h-index was calculated, the h-core articles (those with h or more citations) were specifically assessed to determine citation author position. Novel bibliometric indices were created to reflect the number of h-core articles that accounted for primary (h(p)), senior (h(s)) or internal authorship (h(i)) position. Weighted “involvement factors” for primary (i(p)) and senior (i(s)) author contribution were created to reflect the added value of “enhanced position” authorship in an individual’s h-core publications. c-indices were created to reflect the author’s h-index once augmented by primary (c(p)), senior (c(s)), and overall (c(o)) “enhanced position” authorship. Comparisons were made within each institution and across institutions, according to academic rank (assistant professor, associate professor, professor and chairperson). Results Breakdown by academic rank showed an increasing average h-index progressing from assistant professor through professor rank with no significant difference demonstrated between professor and chair status. This pattern was seen across all departments (aggregate) but with fewer instances of significance at the level of individual departments. After h-index modification, c(p), c(s), and c(o )indices showed a similarly significant trend. As faculty rank increased, there was a significant trend toward increasing numbers of articles with authors in enhanced positions and a higher percentage of articles with the author in a senior position. Academic faculty had higher h, c(p), and c(s )indices than clinical faculty. Evaluation of each individual department revealed no significant trend regarding a department’s higher average c(p) or c(s). Average c-index for a department paralleled the average h-index of that department, with larger departments tending to have larger cumulative h, c(p), c(s,) and c(o) indices. No consistent correlation was seen between mean h-indices and academic rank at an individual departmental level. Conclusions This study examines the academic productivity of a subset of neurosurgical programs in the NYC metropolitan area as a test bed for novel bibliometric indices. h(p), h(i), and h(s) represent the respective number of primary, internal and senior authorship papers that comprise an individual’s h-core papers. c(p), c(s), and c(o), variations of the h-index metric, are designed to more accurately reflect the contributions by primary, secondary and senior authors. Increasing academic rank was associated with an increased number of articles with the author in enhanced positions and a higher percentage of articles in a senior position.